The Effectiveness Of Different Types Of Digital Marketing Channels - Szeker, Marcell (Digital Repository of Theses, 2025)
Digital marketing has become a cornerstone of modern business strategy, offering small businesses opportunities to compete with larger firms through costeffective and measurable channels. This thesis examines the effectiveness of six key digital marketing channels—social media marketing, search engine optimization (SEO), content marketing, email marketing, pay-per-click (PPC) advertising, and influencer marketing—evaluating their mechanisms, reach, and return on investment (ROI). A qualitative methodology was adopted, drawing on secondary data, academic literature, industry reports, and case studies to assess their impact on small business performance. Findings reveal that social media marketing fosters strong brand awareness, customer engagement, and community-building, while SEO provides sustainable visibility and organic traffic at relatively low cost. Content marketing emerges as an essential tool for authority-building and trust, also enhancing SEO and social media strategies. Email marketing consistently delivers among the highest ROI, excelling in customer retention and personalized communication. In contrast, PPC advertising offers immediate visibility but demands careful budget control due to rising costs and competitive pressures. Influencer marketing demonstrates considerable potential in niche markets, though its success depends on authenticity, relevance, and strategic partnership management. The study concludes that a balanced, integrated digital marketing strategy—tailored to the specific goals, resources, and customer base of the small business—achieves the greatest ROI. Practical recommendations include prioritizing SEO and content marketing as long-term investments, leveraging email for retention, and applying PPC and influencer campaigns selectively for short-term impact. By implementing these insights, small businesses can strengthen competitiveness and drive sustainable growth in the digital marketplace.